Systematic review and policy dialogue to determine challenges in evidence-informed health policy-making: findings of the SASHA study - Bahareh Yazdizadeh; Haniye Sadat Sajadi; Farideh Mohtasham; Mahsa Mohseni; Reza Majdzadeh (BMC, 2021)
Abstract Background Various interventions have been undertaken in Iran to promote evidence-informed health policy-making (EIHP). Identifying the challenges in EIHP is the first step toward strengthening EIHP in each country through the design of tailored interventions. Therefore, the current study was conducted to synthesize the results of earlier studies and to finalize the list of barriers to EIHP in Iran. Methods To identify the barriers to EIHP in Iran, two steps were taken: a systematic review and policy dialogue. To conduct the systematic review, three Iranian databases and PubMed, Health Systems Evidence (HSE), Embase, and Scopus were searched. The reference lists of included papers and documentation from some local organizations were hand-searched. Upon conducting the systematic review, given the significance of stakeholders in clarifying the problem of EIHP, policy dialogue was used to complete the list previously extracted and to do advocacy. Selection criteria for the stakeholders included influential and informed individuals from knowledge-producing, knowledge-utilizing, and knowledge-brokering organizations. Semi-structured interviews were held with three important absent stakeholders. Results Challenges specific to Iran that were identified included the lack of integration of the health ministry and the medical universities, lack of ties between health knowledge utilization organizations, failure to establish long-term research plans, neglect of national research needs at the time of recruiting human resources in knowledge-producing organizations, and duplication and lack of coordination in routine data obtained from surveillance systems, disease registration systems, and censuses. It seems that some challenges are common across countries, including neglecting the importance of inter- and intra-disciplinary studies, the capacity of policy-makers and managers to utilize evidence, the criteria for evaluating the performance of policy-makers, managers, and academic members, the absence of long-term programmes in knowledge-utilizing organizations, the rapid replacement of policy-makers and managers, and lack of use of evaluation studies. Conclusions In this study, we tried to identify the challenges regarding EIHP in Iran using a systematic review and policy dialogue approach. This is the first step toward determining the best interventions to improve evidence-informed policy-making in each country, because these challenges are contextual and need to be investigated contextually.